The Implementation Of Psychosocial Rehabilitation In Adolescents Using Drugs With Inefective Coping Problems - Rahayu, Gumelar Zati; Suhanda, Suhanda; Firmansyah, Andan (LPPM STIKes Muhammadiyah Ciamis, 2024)
Objective : Drug abuse in adolescents is a serious problem that affects their physical, psychological, and social health. In addition, the problem of ineffective coping has a frequent impact on drug users. Data from the National Narcotics Agency show that out of 34.7 million drug users in Indonesia, the prevalence of drug attacks in West Java is at 2.45%, with a total of 850 thousand people in the age range of 10-59 years. It is hoped that this can help adolescent drug users overcome ineffective coping problems through better selfunderstanding, managing emotions, improving social skills, and forming healthy groups. Method : This research method uses a case study design. The case study design was chosen because this study aims to gain an in-depth understanding of the application of psychosocial rehabilitation to adolescent drug users with ineffective coping problems. The implementation of this research lasted for 10 days located in Banjarsari District. Result : The results of the case study after being given psychosocial rehabilitation the client's coping becomes effective and regular, the client can assess the positive aspects that can be done. Clients are able to carry out methods of implementing psychosocial rehabilitation. Conclusion and Recommendations : By paying attention to the physical, psychological and social aspects of this process can help adolescents to overcome the problem of ineffective coping. Support from the family and encouragement from the social environment also influence the recovery process.